Optimizing Cash Flow Management and Inventory Control in Engine Power Plant Sales Proposals : A Case Study at Wärtsilä Finland Oy - Dolinin, Vadim (My University, 2025)
This case study investigates how cash flow management and inventory control affect financial risk assessment during sales phase of the Engine Power Plant projects in Wärtsilä Finland Oy. This qualitative research applies inductive approach by conducting semi-structured interviews. Also, a recent sales project showed the real case of the phenomena. The study found that existing cash flow tool in internal software system does not present required picture of the risks related to the projects without payment guarantees. The financial success of these projects depends on how well cash inflow is compared to inventory commitments. This thesis suggested to integrate the handmade tool into the company’s internal system. This would allow proposal departments to improve the accuracy and speed of financial assessments under time pressure. Thus, upgrading existing tool was found to be the essential step in optimizing sales proposals.

Tämä tapaustutkimus tutkii miten kassavirran hallinta ja varastonhallinta vaikuttavat Wärtsilä Finland Oy:n moottorivoimalaitos -projektien myyntivaiheen rahoitusriskien arviointiin. Tämä kvalitatiivinen tutkimus soveltaa induktiivista lähestymistapaa tekemällä puolistrukturoituja haastatteluja. Myös eräs tuore myyntiprojekti toimi käytännön esimerkkinä aiheesta. Tutkimuksessa todettiin, että olemassa oleva kassavirtatyökalu sisäisessä ohjelmistojärjestelmässä ei anna vaadittua kuvaa projekteihin ilman maksutakuita liittyvistä riskeistä. Näiden hankkeiden taloudellinen menestys riippuu siitä, kuinka hyvin kassavirtaa verrataan inventaariositoumuksiin. Tässä opinnäytetyössä ehdotettiin käsin tehdyn työkalun integroimista yrityksen sisäiseen järjestelmään. Näin tarjousosastot voisivat parantaa taloudellisten arviointien tarkkuutta ja nopeutta aikapaineen alla. Näin ollen olemassa olevan työkalun päivittäminen todettiin olennaiseksi askeleeksi myyntitarjousten optimoinnissa.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; fi=Tuotantotalouden ja tietojärjestelmätieteen kandidaattiohjelma|en=Bachelor Programme in Industrial Management and Information Systems|